Polaronic Mechanism of Superconductivity in Cuprates. (30th July 2013) - Chaudhary, Pradeep; Nuwal, Anuj; Tiwari, S. C.; Paliwal, R. K.; Kakani, S. L.
Abstract : A strong polaron pairing model of high-temperature cuprate superconductors is presented. The normal and anomalous one-particle Green's functions are derived from a system with strong electron-phonon coupling. Self-consistent equation for the superconducting order parameter (Δ ) is derived using Green's function technique and following Lang and Firsov transformations. Expressions for specific heat, density of states, free energy, and critical field based on this model have been derived. The theory is applied to explain the experimental results in the systemYBa 2 Cu 3 O 7 - x . There is convincing evidence that the theory is fully compatible with the key experiments.